Zero to Hero - Chee-Ming Chan; Tasnim Zakepeli; Darshinii A. Sivasanmugam; Siti Nur Asyiqin Ahmad Sahlan; Josline John (2023)
This is a collection of personal stories by 54 students from the class of Soil Mechanics & Foundations (Semester 2 Session2021/22), Faculty of Engineering Technology, UTHM. Coming back to the university after the COVID 19 global lockdown, Zero to Hero'takes us on a semester-long journey of the students in learning the Course, individually told in a double section of Strategy and Self Reflection. Strategies were lain and plans were organised to learn the Course effectively in their uniquely personalised approaches (STRATEGY), which were put through self-review at the end of the semester to gauge the outcomes (SELF REFLECTION). Assessment and grades aside, the most significant outcome is but the students' rise above fears and doubts at the beginning of the semester, grappling with the learning process with utmost grit and determination, coming out of it at the end, triumphant with renewed confidence and self-awareness.